Kontribusi Sikap Belajar dan Motivasi Belajar Terhadap Hasil Perkuliahan Bahasa Indonesia Mahasiswa - Uli Wahyuni; Fitra Afrida Amna; Elvina A Saibi (Universitas Batanghari Jambi, 2023)
The learning outcomes obtained by each student are different because the potential possessed by students is different, as well as how to develop their potential. How to develop their potential depends on the desires of each student. This is influenced by the motivation that each student has. Learning attitudes also affect student learning outcomes in Indonesian language learning. A person's attitude to something will be addressed through behavior. Students who are positive about and open to accepting learning will provide encouragement to students to achieve success. The objectives of this study are as follows. (1) Knowing the amount of significant contribution between learning attitudes towards student Learning Outcomes of Indonesian language lectures. (2) Knowing the amount of significant contribution of learning motivation to the learning outcomes of student Indonesian language lectures. (3) Knowing the amount of significant contribution between learning attitudes and motivation to learn together to the learning outcomes of student Indonesian language lectures. This type of research is quantitative with descriptive methods and uses correlation design. The population of this study is all FKIP students of Batanghari University. The sampling technique is carried out by random sampling, namely the sampling of sample members from the population which is carried out randomly. This research instrument is in the form of a questionnaire that has been tested for validity and reliability. The data were analyzed using the Pearson Product Moment (PPM) correlation test, double correlation test, t test, F test, and determinant coefficient formula to determine the magnitude of the contribution of free variables to bound variables, either individually or jointly.The results showed that learning attitudes and learning motivation contributed significantly to student lecture learning outcomes by 20.5%. Thus, these variables have a good influence on the learning outcomes of FKIP students at Batanghari University